Biological safety : principles and practices - Fleming, Diane O.; Hunt, Debra Long (Reference Manual, ASM Press., 2006)
The fourth edition of Biological Safety: Principles and Practices continues the format of the previous edition, focusing closely on infectious and toxic biological agents and their identification and control.